Mac OS X v10.4 system administration reference. - Regan, Schoun; Pugh, David (David A.) (Apple training series., 2006)
Focusing specifically on Account Management and Deploying Mac OS X Server, this comprehensive reference provides in-depth information on Mac OS X Server's technical architecture. System administrators, IT professionals, and Mac enthusiasts will learn the details of how to deploy Mac OS X Server within a multiplatform, heterogeneous environment, and how to manage Mac OS X Server accounts. This is the second of two volumes certified by Apple Computer. Following the learning objectives of the Apple Certified System Administrator exam, this book is a perfect supplement to Apple's own training class and an in-depth technical reference for existing system administrators and engineers.